Aluminum salen and salan complexes in the ring‐opening polymerization of cyclic esters: Controlled immortal and copolymerization of rac‐β‐butyrolactone and rac‐lactide. Issue 5 (5th December 2012) - Cross, Edward D.; Allan, Laura E. N.; Decken, Andreas; Shaver, Michael P.
Abstract Aluminum‐based salen and salan complexes mediate the ring‐opening polymerization (ROP) of rac‐β‐butyrolactone (β‐BL), rac‐lactide, and ε‐caprolactone. Al‐salen and Al‐salan complexes exhibit excellent control over the ROP of rac‐β‐butyrolactone, yielding atactic poly(3‐hydroxybutyrate) (PHB) with narrow PDIs of <1.15 for Al‐salen and <1.05 for Al‐salan. Kinetic studies reveal pseudo‐first‐order polymerization kinetics and a linear relationship between molecular weight and percent conversion. These complexes also mediate the immortal ROP of rac‐β‐BL and rac‐lactide, through the addition of excess benzyl alcohol of up to 50 mol eq., with excellent control observed. A novel methyl/adamantyl‐substituted Al‐salen system further improves control over the ROP of rac‐lactide and rac‐β‐BL, yielding atactic PHB and highly isotactic poly(lactic acid) (Pm = 0.88). Control over the copolymerization of rac‐lactide and rac‐β‐BL was also achieved, yielding poly(lactic acid)‐co‐poly(3‐hydroxybutyrate) with narrow PDIs of <1.10. 1H NMR spectra of the copolymers indicate a strong bias for the insertion of rac‐lactide over rac‐β‐BL. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013